TECHNOLOGICAL PROCESSING OF GRAIN MASS IN A HIGH ELECTRIC FIELD - Usenko, S.; Naumenko, O. (Energy and Automation, 2016)
Here are presented the scheme and description of technological process for grain mass in a high electric field.